A new methodology for the assessing of power losses in partially shaded SPV arrays. (1st October 2021) - de Jesus dos Santos Rodrigues, Marinaldo; Torres, Pedro Ferreira; Barros Galhardo, Marcos André; Chase, Otavio Andre; Monteiro, Weslley Leão; de Arimatéia Alves Vieira Filho, José; Mares, Fabrício Menezes; Macêdo, Wilson Negrão
Abstract -: This paper describes a novel methodology for estimating the shading factor and the irradiance in partially shaded photovoltaic arrays. The results indicate that the monitoring of short circuit currents obtained from the IV curves of shaded and unshaded modules can be used to calculate the overall irradiance on partially shaded and not shaded photovoltaic arrays. This new methodology avoids the need to use several irradiance sensors to map the shaded and unshaded regions. Besides that, this paper presents a simple mathematical model to estimate shading losses on SPV arrays at the points of maximum global and local power. The methodology can be described in five steps: the measurement of the IV curve and cell temperature, pre-processing of the IV curve, calculation of the shading factor and irradiance on the shaded and unshaded areas, use of the photovoltaic array model to obtain the simulated IV curve and the shading level distribution in the array. The proposed model was developed using the methodology presented in this work, demonstrating how useful it can be to validate and develop models applied to evaluate the shading effects. Calculated losses are compared to those obtained with models found in the literature. The proposed model is useful for calculating the instantaneous power losses, requiring less information as input than other detailed models, and requiring low computational eﬀort. Highlights : A novel methodology to evaluate the effect of partial shading on solar photovoltaic arrays. Using ISC extracted from the IV curve found best suited for irradiance estimation on the shading zone. A simplified model for shading losses calculation in SPV arrays is proposed. Estimate shading losses on SPV arrays at the points of maximum global and local power.